Economic Security Outlook for India in a World of Growing Political Uncertainty - Kuznetsova, Natalia Victorovna; Kuznetsova, Ekaterina Vasilievna (Indian Journal of Finance, 2015)
The research paper provided an analysis of India's economy, its domestic issues, and more importantly, its integration with the world economy. The paper described key factors in the nature of Indian participation in international division of labor, discussing both strengths and weaknesses that provide opportunities or dictate India's needs. The analysis of foreign direct investment inflows and outflows is provided, as well as India's trade partnerships: key sectors and key partners. The paper also discussed about the special economic zones in India. India's energy crisis is discussed, and countries that currently play a major role in mitigating that crisis are also presented. The article also pointed out general economic and social situations: as the service sector plays an extremely important role in the Indian economy, the quality and quantity of its labor force were also discussed, and so was the general business environment for domestic and foreign investors. The key points for India's economic security in the nearest future are suggested, and brief geopolitical factors that will shape the strategic choices of India are also presented. In conclusion, the paper presented an outlook on the current situations in India, key economic security priorities, India's international economic partnerships, and vision on strategic partnerships that will mitigate existing risks and promote healthy economic growth.